Evaluation of risk factors for intrapartum caesarean section in low risk multiparous women with prior vaginal deliveries - Vala, Shradhdha M.; Purvi K.Patel (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: In 2015, WHO proposed the use of the Robson classification as a global standard for assessing, monitoring and comparing caesarean section rates both within and between healthcare facilities. Robson’s group 3 and 4 consist of multiparous women with term singleton pregnancies who have previously delivered vaginally and attempts to audit the caesarean sections in these 2 groups may be helpful to reduce primary caesarean sections in multiparous women. Methods: The eligible subjects (belonging to Robson group 3 and 4) were recruited from the labor room of the Obstetrics and Gynecology department of SSG hospital, Baroda. Those who delivered by caesarean section during the study period were enrolled in the study as cases. Those who delivered vaginally immediately following the case formed the controls. Relevant demographic characteristics, parity, interval time between prior birth, history of macrosomic birth, cervical dilatation at the admission to the hospital, obstetric and neonatal outcomes were obtained and analyzed.. Results: On performing multivariate regression, age, birth weight of previous child, time since last delivery, cervical dilatation were found to be significant independent risk factors for LSCS after adjusting for confounding factors. The most common indication for caesarean section was fetal distress with meconium stained liquor. Conclusions: In low risk multiparous women with previous vaginal delivery, Maternal age, birth weight of previous child, time since last delivery and cervical dilatation were significant independent risk factors of LSCS. Gestational age, parity, BMI and labor induction were not found to increase the risk of caesarean delivery.